PERANCANGAN CONTENT MANAGEMENT SYSTEM (CMS) WEBLOG ORGANISASI MENGGUNAKAN PENDEKATAN TEKNIK MODEL VIEW CONTROLLER (MVC) - Agung Sasongko (Universitas Bina Sarana Informatika, 2013)
Abstract Content Management System (CMS) as an application that can help someone less possess technical expertise in making the website to make the website easy and practical. Basically someone with CMS simply make setting up and managing the website content as you wish. There are so many outstanding CMS, as well as plugins to enhance the capabilities of the website, but the outstanding plugins also raises questions about data safety because the plugins are made by people who may have other interests against those who use artificial plugins. Another problem arises is on developing the ability of CMS would have to master the flow of CMS rules. Problems can be solved when building CMS independently. Development of CMS in this study using techniques Model View Controller (MVC) to classify the database encoding, display and logic control applications in order to facilitate the further development of the pattern that has been established.Key words: CMS, website, model view controller